2008
DOI: 10.1152/ajpcell.00330.2007
|View full text |Cite
|
Sign up to set email alerts
|

The class V myosin motor, myosin 5c, localizes to mature secretory vesicles and facilitates exocytosis in lacrimal acini

Abstract: Marchelletta RR, Jacobs DT, Schechter JE, Cheney RE, Hamm-Alvarez SF. The class V myosin motor, myosin 5c, localizes to mature secretory vesicles and facilitates exocytosis in lacrimal acini. Am J Physiol Cell Physiol 295: C13-C28, 2008. First published April 23, 2008 doi:10.1152/ajpcell.00330.2007.-We investigated the role of the actin-based myosin motor, myosin 5c (Myo5c) in vesicle transport in exocrine secretion. Lacrimal gland acinar cells (LGAC) are the major source for the regulated secretion of protei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
46
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(52 citation statements)
references
References 56 publications
(92 reference statements)
5
46
1
Order By: Relevance
“…We favor such a mechanism, because myosin V family motors have been shown to mediate secretory vesicle transport both in Saccharomyces cerevisiae, in which actin cables generated by the formin Bni1-related1 (Bnr1), located at the bud neck, serve as tracks for vesicle transport to the growing bud (22), and in our previous study of secretion via Dia-generated cables in Drosophila tubular organs (11). Furthermore, the velocity of vesicle movement over actin bundles that we report is similar to the measured velocity of vesicle transport via myosin Vc, the predominant myosin V isoform in the exocrine pancreas (23,24).…”
Section: Discussionsupporting
confidence: 84%
“…We favor such a mechanism, because myosin V family motors have been shown to mediate secretory vesicle transport both in Saccharomyces cerevisiae, in which actin cables generated by the formin Bni1-related1 (Bnr1), located at the bud neck, serve as tracks for vesicle transport to the growing bud (22), and in our previous study of secretion via Dia-generated cables in Drosophila tubular organs (11). Furthermore, the velocity of vesicle movement over actin bundles that we report is similar to the measured velocity of vesicle transport via myosin Vc, the predominant myosin V isoform in the exocrine pancreas (23,24).…”
Section: Discussionsupporting
confidence: 84%
“…In previous studies, we showed that only 20 -30% of total cellular syncollin-GFP is released during a typical stimulation period with CCH (14,25). This plotting format thus enables detection of differences between treatment groups and enables clear comparison to previous work in which the role of other effectors in exocytosis of syncollin-GFP (Myo5C, Rab3D, actin filaments) has been probed (14,25,29). In data plots, values were expressed as a percentage increase above the total release from stimulated acini of cells expressing WT in the presence of CCH at the maximal time of release (30 min), normalized to 1.…”
Section: Methodsmentioning
confidence: 78%
“…As a measure of regulated secretion, syncollin release was measured in LG acinar cell cotransduced with Ad-syncollin-GFP and the Xp-WT, -CA, or -DN constructs as described previously (20,24,29). The bathing media, which is continuous with the apical lumina of the cultured cells, was collected at time points after CCH addition.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations